Método gráfico usando vecindades para detectar outliers (2015)
We propose a new graphical method to help us to uncover  potential outliers in multivariate samples. The idea behind the method is to analyze the behavior of a growing neighborhood of each data point. This method is very robust and allows to find outliers in very complex structures.